Integrasi Ajaran Filsafat Agama Dalam Pendidikan Anak Usia Dini Untuk Meningkatkan Toleransi Dan Empati - Rohayani, Farida (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2025)
This study aims to explore the role of integrating religious philosophy teachings in early childhood education (PAUD) as an effort to increase the values of tolerance and empathy in children. Religious philosophy offers universal principles that can be applied in the context of children's character education, including values such as compassion, justice, and respect for diversity. Through a qualitative approach, this study observes the process of integrating religious philosophy values into learning activities in PAUD and its impact on children's social behavior. The results of the study indicate that with an approach based on stories, games, and concrete experiences, children can absorb and practice the values of tolerance and empathy in their daily lives. In addition, this approach also shows that introducing these values strengthens children's social interactions, increases their awareness of differences, and forms better prosocial behavior. Although there are challenges in implementation, such as limited teacher understanding and resistance to diversity, these findings indicate that integrating religious philosophy into early childhood education can be an effective strategy to shape a more tolerant and empathetic future generation. This study suggests the need for more inclusive curriculum support, training for educators, and active involvement of parents and communities to support this integration process.